THE IMPACT OF CUSTOMER SATISFACTION, CUSTOMER EXPERIENCE, E-SERVICE QUALITY TO CUSTOMER TRUST IN PURCHASING DIGITAL PRODUCT AT THE MARKETPLACE - Halim, Erwin; Claudia, Lucyana; Hebrard, Marylise (Jurnal Aplikasi Manajemen, 2023)
One of the emerging business model changes is the emergence of the e-commerce industry. E-commerce Company can develop if customers are satisfied and the service quality is also good. The subject of this research is about the impact of Customer Satisfaction, Customer Experience, and Electronic Service Quality on Customer Confidence in Buying Digital Products in Each Marketplace. Therefore, this study aims to analyze whether these variables have a significant effect on customer trust in buying digital products in each marketplace. The sampling technique used in this study was a purposive sampling technique which was selected based on respondents who were willing to fill out a questionnaire and met predetermined sample criteria. The hypothesis proposed in this study was tested using multiple linear regression tests. The results showed that Customer Satisfaction, Customer Experience, Electronic Service Quality have a significantly positive effect on Customer Confidence in Buying Digital Products in Each Marketplace. Marketplace must ensure that customer experience, electronic service quality, and customer satisfaction are met so as to strengthen customer confidence in buying digital products.